The sensory approach in the architecture of Fernand Pouillon.: The revelations of the texts - ZINEDDINE , Sara; BELAKEHAL , Azeddine (Journal of Human Sciences, 2021)
This research concentrates on the exploration of the contemporary architectural heritage of Fernand Pouillon in Algeria independent of sensory point of view. It is a question of drawing the different evocations of the senses, the sensitive and physical phenomena visual, corporal, tactile, and auditory. By means of a subjective reading of textual information in the quotes of Fernand Pouillon. The architecture of Fernand Pouillon is studied through the application of textual analysis method on the: quotes, and interesting terms which sometimes are intended to feed a clear or implicit sense of the sensory aspect in their conceptual approach. All the information collected was identified and classified quantitatively to show the plurality of hints among the different types of physical environments recommended by Fernand Pouillon.